Exploration of Muslim Guests' Preferences and Expectations towards Muslim-Friendly Hotel Facilities and Services at Horison Aziza Solo - Marcelina, Marcelina; Palupiningtyas, Dyah (Journal of Business Management and Economic Development, 2025)
This study aims to explore Muslim guests' preferences and expectations regarding Muslim-friendly hotel facilities and services at Horison Aziza Solo. Utilizing a qualitative approach, the research involved 25 Muslim guest participants selected through purposive sampling. Data were collected through semi-structured interviews and direct observations, then analyzed using thematic analysis. The findings indicate that the availability of halal food and worship facilities are the primary preferences, with importance levels of 100% and 95%, respectively. The largest gap was identified in the aspect of separating facilities based on gender (15%), while staff services exhibited the smallest gap. Horison Aziza Solo has demonstrated strong performance in implementing the Muslim-friendly hotel concept, with key strengths in its strategic location and management commitment. However, there is still a need for improvement in service consistency and facility optimization. This study contributes theoretically to the development of halal tourism literature and offers practical implications for the management of Muslim-friendly hotels in Indonesia.